PEMETAAN TINGKAT KONSENTRASI PARTIKULAT AKIBAT AKTIVITAS TRANSPORTASI DI WILAYAH SURABAYA PUSAT - Mohammad Razif (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2006)
Particulate that has diameter less than 10 u (PM10) is known as the dominant transportation air pollutant in Surabaya City. This research was done with counting particulate concentration level as an early stage in providing a distribution pattern map and air pollution control. The research was implemented in road segment which was predicted as the highest pollutant source. The roads included Basuki Rahmat, Gubernur Suryo, Panglima Sudirman, Pemuda and Kayun, Surabaya. The sampling method followed the East Java Province Governor Decree No128/1997. The research resulted in particulate concentration, which exceeded the ambient air quality standards according to Indonesian Government Regulation No 41/1999 of 150 μg/m3.